Sistem Pemberian Upah Untuk Meningkatkan Kesejahteraan Anak Buah Kapal Perspektif Ekonomi Syariah - Elma Suci Oktaviyani; Ratna Yunita (Niqosiya: Journal of Economics and Business Research, 2024)
Wages or ijarah are an important component in the world of work because wages are directly related to workers' welfare. According to Islamic economic theory, wages must contain the principle of justice in them. This research aims to determine and analyze the wage system to improve the welfare of Putra Samudra's crew members and to determine and analyze the implementation of the ship crew's wage system from a Sharia economic perspective. This research is field research using qualitative methods. The research results show that 1) The wage system implemented on the Putra Samudra Ship uses a time-term wage system consisting of daily wages and weekly wages. With these two systems in place, the amount of wages that must be paid by the Putra Samudra ship is not yet high when compared to the risks faced by the crew. However, to improve the welfare of fishermen, ship owners use a bonus wage system that can be used to meet the needs of fishermen and their families. 2) Based on the Sharia economic perspective regarding the implementation of the wage system on the Putra Samudra ship, in practice there is injustice in the giving of wages to the crew by the ship owner, namely the equality of nominal bonus wages between diligent fishermen and lazy fishermen.